МАРКЕТИНГОВЕ ДОСЛІДЖЕННЯ ПОВЕДІНКИ СПОЖИВАЧІВ В СЕРЕДОВИЩІ ЦИФРОВОЇ ІНФРАСТРУКТУРИ - Yushkevych, Olena; Vikarchuk, Olga; Zaburmekha, Yevhena (Zhytomyr Ivan Franko State University, 2023)
The article is devoted to marketing research on consumer behaviour in the environment of digital infrastructure. It has been established that marketing research of consumer behaviour in the environment of digital infrastructure models strong systems of interaction with consumers by accurately defining their needs and requests, individualising products and services, operational tracking, and responding to the behaviour of each specific consumer. Research has shown that in a digital infrastructure environment, price is not the primary factor determining choice. First of all, the consumer correlates the characteristics and properties of the goods with his ideal ideas about them (the standard of consumer properties), and in the event of a match, he proceeds to evaluate the possibilities of its purchase, taking into account the price and available income. It has been proven that the environment of the digital infrastructure determines a rational consumer choice under the conditions of a high speed of the reproduction cycle, which singles out time as the main valuable resource, which is associated with the growth of alternative costs of the consumer demand formation process and its implementation. It was found that the development of digitalization has an ambiguous effect on the behaviour of the modern consumer: on the one hand, the possibilities of consumer access to new goods and services are expanding in the shortest possible time, and on the other hand, the level of consumer requirements is increasing, which increases competition between manufacturers and stimulates them to search for new forms of interaction with the consumer. The stages of making a purchase decision by a consumer and the possibility of influence on their opinion by digitalization tools are outlined: awareness of the need, search for information on how to solve problems, evaluation of found solutions to the problem, purchase decision, reaction to the purchase. The elements of digitalization strategies for purchasing behaviour in the context of digital transformation are defined. The services of digital presentation of the product and delivery of goods have been updated, and the frequency of online purchases has increased due to changes in the structure of consumption. It has been proven that the active development of digital technologies and methods of their use necessitated an evolutionary transition from the category of e-services to “digital services”, which take into account the complex influence of the Internet and accompanying digital technologies on the formation of modern business models of companies and the format of their interaction with product consumers and services.